2019
DOI: 10.12659/msm.916886
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1α (HIF-1α) Promotes Hypoxia-Induced Invasion and Metastasis in Ovarian Cancer by Targeting Matrix Metallopeptidase 13 (MMP13)

Abstract: Background: Hypoxia promotes cancer progression. Hypoxia-inducible factor-1a (HIF-1a) has been reported to enhance tumor invasion and metastasis via activating downstream genes, such as matrix metalloproteinases (MMPs). The purpose of this study was to explore the probable roles of HIF-1a and MMP13 in the invasion and metastasis of ovarian cancer under hypoxic conditions. Material/Methods: The expression of HIF-1a and MMP13 protein were detected with immunohistochemistry staining in ovarian cancer tissues, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
(27 reference statements)
2
27
0
Order By: Relevance
“…In non-malignant cells such as smooth muscle and adipocytes, hypoxia-induced DPP4 shedding is mediated by increased activity of MMPs 1, −2, and −14 [ 15 ]. Our data suggests that the mechanism of DPP4 release from cancer cells is likely to be different, involving proteolytic release and inactivation mediated by at least MMP10 and MMP13, which directly supports recent evidence that hypoxia promotes ovarian cancer cell invasion via an MMP-13 mediated mechanism [ 30 ]. By analogy, DPP4 is shed from the surface of CD4+ T cells by kallikrein-related peptidase 5 (KLK5) [ 31 ], and in hepatoma cells Serpin B3 induces overexpression of inactive DPP4 [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…In non-malignant cells such as smooth muscle and adipocytes, hypoxia-induced DPP4 shedding is mediated by increased activity of MMPs 1, −2, and −14 [ 15 ]. Our data suggests that the mechanism of DPP4 release from cancer cells is likely to be different, involving proteolytic release and inactivation mediated by at least MMP10 and MMP13, which directly supports recent evidence that hypoxia promotes ovarian cancer cell invasion via an MMP-13 mediated mechanism [ 30 ]. By analogy, DPP4 is shed from the surface of CD4+ T cells by kallikrein-related peptidase 5 (KLK5) [ 31 ], and in hepatoma cells Serpin B3 induces overexpression of inactive DPP4 [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…As shown, in both experimental conditions we observed a variable number of deregulated genes, mainly related to EMT, cellular adhesion, extracellular matrix remodeling, invasion and other cell activities, while a distinct cluster of genes was observed to be deregulated exclusively in cells co-cultured with ML-Ddx4 + cells from the A2 patient ( Figure 5 c). In particular, upregulated DEGs included SIRT1 , which is involved in stemness [ 28 ] and chemoresistance [ 29 ], SNAIL2, which participates in EMT and collagen remodeling [ 30 , 31 ], and SIRT2 , CTGF , IL-11 and MMP13 , involved in cell migration, invasiveness as well as resistance to platinum and paclitaxel [ 32 , 33 , 34 , 35 , 36 ]. Other upregulated DEGs, such as MCM-6 , TGFB-1 , HMGA2 and FOXM1 , are involved in similar cancer-related processes [ 37 , 38 , 39 , 40 , 41 , 42 ], while downregulated DEGs, such as LOX and TIMP-1 (which are associated with poor cancer prognosis [ 43 , 44 , 45 ]), were observed in A2780 co-cultured with both A1 and A2 derived ML-Ddx4 + cells.…”
Section: Resultsmentioning
confidence: 99%
“…By performing bioinformatics analysis, we revealed that FGF11 was closely correlated with hypoxia signaling, and furthermore, qRT-PCR analysis and western blot all validated that FGF11 could regulate HIF-1α expression positively. Since HIF-1α has been acted as an indispensable signaling transduction mediators by regulation of their target genes, thereby affecting cell function and fate [37][38][39][40]. Rescue experiments further suggested that knockdown of HIF-1α diminished the oncogenic role of FGF11 in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%